Multi-temporal airborne structure-from-motion on caldera rim: Hazard, visitor exposure and origins of instabilities at Piton de la Fournaise. (April 2019) - Derrien, Allan; Villeneuve, Nicolas; Peltier, Aline; Michon, Laurent
Piton de la Fournaise is one of the world's most active and visited volcanoes. Its summit crater (Cratère Dolomieu), the main tourist attraction, underwent a major caldera collapse in 2007 and its rim is not yet stabilized. In order to assess the caldera rim instability risk for visitors, we followed its structural evolution from 2007 to 2015. Using aerial photogrammetry campaigns, we mapped the unstable sites very precisely, carried out a quantitative analysis of the temporal evolution of these instabilities, and assessed the risks for visitors. Considering the 2008–2015 period, four sites close to the crater's edge showed significant horizontal ground motion (0.5–2 m), fracture widening (average of 0.3–0.56 m) and large-scale mass wasting volumes (total of 1.8±0.1 × 10 6 m 3 ). We infer two different processes at work: (1) to the west and north, toppling of the basalt units occurs after periods of fracture widening due to the combined effect of magmatic intrusions and long-term inflation/deflation cycles; (2) to the south and east, parts of the caldera rim slowly slide towards the caldera centre, with significant accelerations during periods of enhanced volcanic activity (in 2008–2010 and 2014–2015). The official observation platform is the most stable zone to overlook the Cratère Dolomieu. By contrast, the most frequently visited area of the rim (northwest) outside the official platform is also the most unstable.